MARRIAGE ISBAT IN QIYAS PERSPECTIVE - Achmad, Muhammad Thamrin Thamrin; Sultan, Lomba; Bakri, Muammar Muhammad; Hasan, Hamzah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2020)
The main problem discussed in this dissertation is how the implementation of qiyas for marriage isbat (confirmation of marriage). This dissertation discusses about marriage isbat from qiyas perspective, analysing three sub-problems which are the focuses of this study; first, what factors that highly influence isbat of marriage in Makassar Religious Court. Second, how Judge’s consideration in the case isbat of marriage, and third, how is the implementation of qiyas related to the case of marriage sibat in Makassar Religious Court. This research is a field study. Data sources were obtained during the field research at Makassar Religious Court by doing an interview with the judges. The data was analyzed by deductive method and presented descriptively using normative, juridical, sociological and philosophical approaches. Theories used in analyzing data were theories of justice, certainty and expediency, judges, existence, progressive law, in order to implement isbat of marriage in Makassar Religious Court. The results show that the number of marriage isbat is still high in Makassar Religious Court which is driven by some factors, for instance: the case of spouses asked for marriage certificate (Marriage contract), spouses who asked for jointed-property, children who need birth certificate, or inheritance purpose. Submission of marriage isbat application to religious court is in line with the law No. 1 of 1974, Article 2 Paragraphs (1) and (2) of Marriage Compilation of Islamic Law Article 7 Paragraph (3) letter d. The application for isbat of marriage which was filed with the court and consideration of the judge the judge’s consideration in granting the divorce was not bound by positive law alone, but also the consideration of justice, the sociology of law and the public good. The implication of this study recommends the importance of strengthening regulations that can accommodate present and future problems to avoid greater harm so that the problem of "Sirri marriage" that increases can be avoided. The importance of tightening up the conditions in examining the Marriage isbat case and the need for a reconstruction of Law Number 1 of 1974 Article 2 paragraph (2), Regarding Marriage in conjunction with Presidential Instruction Number 1 of 1991 Article 7 Paragraph (3) letter d Regarding Compilation of Islamic Law.